Intercultural mediation: Social, linguistic and psychometric considerations - Rubenfeld, Sara (University of Ottawa (Canada), 2009)
Educational research investigating second language (L2) learning proposes that interculturally competent individuals have the capacity to act as mediators during situations of conflict between members of distinct cultural communities (Alred & Byram, 2002; Gohard-Radenkovic, Lussier, Penz & Zarate, 2004). The following studies aim to systematically investigate this proposal. The first study examines the linkages between aspects of language learning (e.g., L2 contact and confidence) and the use of mediation behaviours among a sample of minority group members. The results indicate a general need for a strong first language identity in order to become involved as a mediator in a conflict scenario. However, the results also point to the need for further assessment of the measure of intercultural mediation. The second and third studies respond to this latter issue through use of modern and classical test theory approaches to instrument assessment among both majority and minority group members. In particular, the second study points to a need to distinguish between the status (minority vs. majority) of the groups involved in the conflict scenarios as well as whether members of the witness' in-group are perpetrating or victims of discrimination. Informed by the results of the second study, the third study outlines the development and assessment of a revised version of the Intercultural Mediation Measure. Following these assessments of the intercultural mediation measure, the final study explores the relative importance of status (minority vs. majority) and role (perpetrator vs. victim) in the prediction of intercultural mediation behaviours and the predictive capacity of first and second language attitudes and representations in the use of nondiscriminatory behaviours. Among a host of revealing results, the analyses indicated a trend of greater mediational involvement in conflict scenarios when the in-group is perpetrating the conflict toward a positively viewed outgroup. This research speaks to the capacity individuals have to demonstrate and encourage positive intercultural relations. The results are discussed in the context of L2 learning, intergroup theory, and directions for future research.
Keywords: Language, Linguistics.; Psychology, General.